2014
DOI: 10.1039/c4cp01948b
|View full text |Cite
|
Sign up to set email alerts
|

Reduction mechanisms of additives on Si anodes of Li-ion batteries

Abstract: Solid-electrolyte interphase (SEI) layers are films deposited on the surface of Li-ion battery electrodes during battery charge and discharge processes. They are due to electrochemical instability of the electrolyte which causes electron transfer from (to) the anode (cathode) surfaces. The films could have a protective passivating role and therefore understanding the detailed reduction (oxidation) processes is essential. Here density functional theory and ab initio molecular dynamics simulations are used to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
97
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(110 citation statements)
references
References 40 publications
(146 reference statements)
13
97
0
Order By: Relevance
“…A number of FEC decomposition routes have been proposed and most include LiF and CO 2 (or Li 2 CO 3 ). 15,[19][20][21] There have been claims in the literature that LiF is central to FEC's benefit, 15,21 which would suggest F-containing additives as beneficial to Si cycling. On the other hand VC is also seen as beneficial to Si cycling and does not contain any F. 22 In screenings of electrolyte additives, VC was shown to lead to considerable gassing with ongoing cycling 23 and CO 2 is part of proposed decomposition routes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of FEC decomposition routes have been proposed and most include LiF and CO 2 (or Li 2 CO 3 ). 15,[19][20][21] There have been claims in the literature that LiF is central to FEC's benefit, 15,21 which would suggest F-containing additives as beneficial to Si cycling. On the other hand VC is also seen as beneficial to Si cycling and does not contain any F. 22 In screenings of electrolyte additives, VC was shown to lead to considerable gassing with ongoing cycling 23 and CO 2 is part of proposed decomposition routes.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand VC is also seen as beneficial to Si cycling and does not contain any F. 22 In screenings of electrolyte additives, VC was shown to lead to considerable gassing with ongoing cycling 23 and CO 2 is part of proposed decomposition routes. 20 FEC can also lead to gassing particularly at high temperatures with CO 2 as the main component. 24 The present results suggest that the possible production of CO 2 by FEC and VC should be considered when considering mechanisms by which they improve the cycle life of Si-based materials.…”
Section: Discussionmentioning
confidence: 99%
“…22,[26][27][28]30,31,36,[46][47][48][49] A mechanism which would be consistent with this β-value will be presented below. Another important aspect of the FEC consumption analysis in Si-Li vs. Li-Li cells is that the FEC consumption per electrode during charge/discharge cycling only depends on the overall exchanged coulombs.…”
Section: Cellmentioning
confidence: 99%
“…It will be shown that FEC nearly suppresses the reduction of any other electrolyte component, which is consistent with the previous literature and suggests that the rate of FEC reduction is greater than the reduction of EC and linear carbonates. [26][27][28][29][30][31] Furthermore, due to the continuous consumption of FEC quantified by 19 F-NMR, the number of charge/discharge cycles over which silicon anodes can by stabilized by FEC is directly proportional to the total moles of FEC per gram of anode electrode, rather than the FEC concentration in the electrolyte. As a consequence, 10-20% wt FEC additive are highly effective when examined at the high electrolyte/active material weight ratios commonly used in small-scale test cells (e.g., coin cells), but are predicted to not provide long-term protection under the much lower electrolyte/active material weight ratios used in commercial cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation